Implementation Of Transformation Services To HKBP Servants In The Digital ERA: Service To Servants Of District XII Tanah Alas - Siregar, Nurliani; Siregar, Hisar; Nainggolan, Justinus Ray; Nababan, Melissa Feblistira; Sibarani, Rohit Yoben (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
The transition to digital approaches in church ministry has become imperative due to the swift advancement of information technology. This community engagement initiative was designed to strengthen the digital skills of HKBP ministry personnel in District XII Tanah Alas through structured training and intensive guidance. The program was executed through interactive presentations, focus group discussions (FGD), practical simulations involving digital tools, and evaluations conducted before and after the activities. Findings revealed that participants’ baseline digital capabilities were generally at a low to moderate level, yet experienced notable improvement following the intervention. Church staff began to exhibit proficiency in embedding digital technologies into everyday ministry, including using Zoom for virtual worship, leveraging social media for church-related communication, and employing applications for managing congregation data. The participants’ active involvement demonstrated their eagerness for a ministry model that is both adaptive and contextually grounded. This initiative further emphasized the long-term promise of digitalization in addressing geographical barriers and broadening the scope of church outreach. Sustained progress requires ongoing training and institutional backing to maintain relevance and coherence throughout the transformation journey. In conclusion, this initiative marks a foundational step for HKBP in cultivating a digitally-driven ministry ecosystem anchored in theological principles and cultural heritage.